Business feasibility analysis (UMKM) kripang products (kripik pangsit) with strategy e-commerce marketing among students - Ng, Hana; Husein, Alice Erni; Wiryanto, Ricky (Institute of Computer Science (IOCS), 2024)
This research aims to evaluate the feasibility of the kripang product business from market, financial, environmental & socio-cultural, operational, legal and technical aspects that are relevant for starting this business. The methodology used in this research includes descriptive analysis to identify the market potential for kripang products among students as well as SWOT analysis to assess strengths, weaknesses, opportunities and threats that may affect this business. The research results show that students are a promising market segment for kripang products, especially if supported by an effective e-commerce marketing strategy. Researched consumer preferences highlight the need for quality, innovative, and easily accessible chipping products online. Financial analysis shows attractive revenue prospects with acceptable profit margins for UMKM business players. The UMKM business for kripang products with an e-commerce marketing approach offers significant opportunities in the student market. Keys to success include a good understanding of market preferences, implementation of appropriate marketing strategies, and careful financial management.